Nanophotonics Enable Targeted Photothermal Silencing of Nociceptor Neurons. Issue 14 (23rd February 2022) - Roversi, Katiane; Tabatabaei, Maryam; Desjardins‐Lecavalier, Nicolas; Balood, Mohammad; Crosson, Theo; Costantino, Santiago; Griffith, May; Talbot, Sebastien; Boutopoulos, Christos
Abstract: The sensory nervous and immune systems work in concert to preserve homeostasis. While this endogenous interplay protects from danger, it may drive chronic pathologies. Currently, genetic engineering of neurons remains the primary approach to interfere selectively with this potentially deleterious interplay. However, such manipulations are not feasible in a clinical setting. Here, this work reports a nanotechnology‐enabled concept to silence subsets of unmodified nociceptor neurons that exploits their ability to respond to heat via the transient receptor potential vanilloid type 1 (TRPV1) channel. This strategy uses laser stimulation of antibody‐coated gold nanoparticles to heat‐activate TRPV1, turning this channel into a cell‐specific drug‐entry port. This delivery method allows transport of a charged cationic derivative of an N‐type calcium channel blocker (CNCB‐2) into targeted sensory fibers. CNCB‐2 delivery blocks neuronal calcium currents and neuropeptides release, resulting in targeted silencing of nociceptors. Finally, this work demonstrates the ability of the approach to probe neuro‐immune crosstalk by targeting cytokine‐responsive nociceptors and by successfully preventing nociceptor‐induced CD8 + T‐cells polarization. Overall, this work constitutes the first demonstration of targeted silencing of nociceptor neuron subsets without requiring genetic modification, establishing a strategy for interfering with deleterious neuro‐immune interplays. Abstract : This work reports a nanotechnology‐enabled strategy to silence subsets of unmodified nociceptor neurons. It uses laser stimulation of neurons targeted with gold nanoparticles to heat‐activate TRPV1, turning this channel into a cell‐specific entry port for silencing drugs that block neuropeptide release (i.e., communication with other cells). This work establishes a paradigm for interfering with deleterious neuro‐immune interplays.